Fusion of genes encoding Escherichia coli heat-stable enterotoxin and outer membrane protein OmpC. - Saarilahti, H T (1989)
The OmpC outer membrane protein of Escherichia coli was used as a carrier molecule for the nonimmunogenic heat-stable enterotoxin STa. Two fragments of different lengths of the gene encoding STa were fused in vitro to the 3' terminus of the truncated ompC gene. The resulting OmpC-STa hybrid proteins could be detected by L-[35S]cysteine labeling, and they were processed and thus exported. All synthesized hybrid protein remained cell bound and was found by fractionation mainly in the periplasm. Immunoblot analysis showed that the hybrid proteins reacted in vitro both with anti-OmpC and anti-STa antibodies, and immunization of rabbits evoked an antibody response to either of these proteins.